Hybrid Software and Systems Development in Practice: Perspectives from Sweden and Uganda - Kanagwa, Benjamin; Hebig, Regina; Heldal, Rogardt; Knauss, Eric (Springer, Cham, 2017)
Many organizations are adapting the use of hybrid software development approaches by combining traditional methods with flexible agile practices. This paper presents the initial results from the survey on the use of hybrid software and systems approaches. The results are from twenty one respondents from Sweden and Uganda. Our results show that the iterative model is the most widely used process model in both Sweden and Uganda. However, the traditional process models are also used in combination with the more agile models like Scrum. From the results, we also show that the large sized companies face the biggest problems during implementation of agility since they have to adhere to standards and control measures.
Keywords: Software process; Hybrid development approaches